Impact of Climate-Smart Agriculture on Smallholder Income and Food Security: Evidence from Propensity Score Matching Analysis - Zeng, Lili; Lettathakornkit, Tippawan (Research on World Agricultural Economy, 2026)
Global climate change poses severe challenges to agricultural production, with climate-smart agriculture emerging as a key response strategy. However, insufficient empirical evidence exists regarding its causal effects on smallholder income and food security. This study surveyed 712 farming households in Southwest China from July to September 2023, using propensity score matching to evaluate climate-smart agriculture technology adoption impacts. The research constructed a comprehensive adoption index including 8 core technologies such as conservation tillage, stress-resistant varieties, and water-saving irrigation. Results show 48% of farmers adopted these technologies. Technology adoption increased average annual household income by 5.16 thousand yuan (23.8% increase) and improved food security scores by 1.74 points (10.4% improvement). Income growth primarily came from crop income increases (3.89 thousand yuan) and livestock income increases (0.98 thousand yuan), with no significant changes in non-agricultural income. Heterogeneity analysis revealed stronger effects among large-scale farmers (6.93 thousand yuan), highly educated farmers (6.28 thousand yuan), and cooperative members (6.41 thousand yuan). Sensitivity analysis indicated robust conclusions with Γ values of 1.65 (income) and 1.42 (food security). Climate-smart agriculture adoption significantly improves smallholder welfare, but effects vary across groups, suggesting the need for differentiated approaches, including enhanced technical training, improved financial services, and farmer organization promotion. This study advances technology adoption theory by showing that benefits depend on complementary assets. Limitations include cross-sectional design and geographic specificity. ER